History and Contributions in Building a Modern Society Perspective of Ibn Kathir's Tafsir - Meirando Rukhuz; Azzahra Zulfi Zulfiah; Wafik Azizah; Muhammad Fadli; Ahmad Yusam Thobroni (al-Afkar, Journal For Islamic Studies, 2024)
Whichever perspective is used is the authority of each person in understanding the Qur'an, what is mandatory is studying the meaning contained in the verses of the Qur'an, both from a historical and other perspective. The purpose of this writing is to explain an understanding of history based on the verses of the Koran, which is the basis for thinking for Islamic historians. The method used in this research is a historical approach, which involves interpretation and collaboration. This article uses Ibn Kathir's book of tafsir as a reference for interpreting the verses of the Qur'an. Muslims are obliged to read history, because to increase self-confidence through the stories contained in it, the verses of the Qur'an provide an overview of the changes that have occurred in human life as a contribution to building a modern society with the perspective of the Qur'an. 'an starting from its initial emergence, development, peak of progress, setback, until collapse.